A Meta-Analysis of Nutritional Supplementation for Management of Hospitalized Alcoholic Hepatitis - Ramy Antar; Phil Wong; Peter Ghali (Canadian Journal of Gastroenterology)
BACKGROUND: Alcoholic liver disease (ALD) is associated with a high risk of morbidity and mortality. Malnutrition accompanies this condition and may be both a consequence of and contributor to the pathology. Many trials have investigated the benefits of providing supplemental nutrition in the management of patients with ALD. The present study is a meta-analysis of the available evidence.